Assessing the Accuracy of Two Dental Age Estimation Techniques—London Atlas and Demirjian’s Methods in Bengaluru Children and Young Adults: A Cross-sectional Study - Umapathy Thimmegowda; Sanchitha Venkatahanumaiah; Jaya A Ramachandra; Amrutha Ujjamma Bennehalli (Journal of South Asian Association of Pediatric Dentistry)
Background: Age estimation is also done on living people in medicolegal cases, including child labor, rape, child marriages, and illegal immigration without sufficient approved documentation. Aim: The aim of the present study was to compare the relative effectiveness of two alternative approaches—London Atlas and Demirjian’s methods—in estimating a person’s chronological age in a sample population of Bengaluru residents. Materials and methods: From the database archives of the Dental College and Hospital, Bengaluru, and five private diagnostic facilities in Bengaluru, 464 inhabitants of Bengaluru, aged 3–18, had radiographs selected for the study. There was a record of the sex, birth date, and image data. Using deidentified orthopantomograms (OPGs), two certified examiners evaluated the dental age estimation. Both examiners concurrently analyzed and graded the stages of tooth development and eruption. Results: There is a substantial positive and statistically significant correlation (p < 0.05) between chronological age and both biological age measures. Conclusion: The association between Demirjian’s age and chronological age is marginally stronger than the relationship between the ages of the London Atlas and Demirjian.